PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Kasus pada PT. Garuda Indonesia Rute Penerbangan Internasional) - Hara Paradisa Santoso; Widayanto Widayanto (Universitas Diponegoro, 2017)
This research is motivated by the escalation of public interest of going abroad byusing airpane as the transportation means. The purpose of this research is to determine thedirect influence and indirect influence between Customer Relationship Management variableand Service quality variable as x variable to customer loyalty as y variable through customersatisfaction as z variable.. The result shows Customer Relationship Management does not havedirect influence to customer loyalty 0.651. Customer satisfaction has direct influence tocustomer loyalty 2.773. Service quality has direct influence to customer loyalty 2.093.Customer relationship management has direct influence to customer satisfaction 2.009.Service quality has direct influence to customer satisfaction with 6.587. The sobel test resultshows there is no influence between Customer Relationship Management to customer loyaltythrough customer satisfaction 1.571. There is direct influence of service quality to customerloyalty through customer satisfaction 2.532. The suggestion is Garuda Indonesia shouldincrease the CRM system and increasing the service quality